BI 6727 and GSK461364 suppress growth and radiosensitize osteosarcoma cells, but show limited cytotoxic effects when combined with conventional treatments. Issue 1 (January 2015) - Bogado, Rodrigo F.E.; Pezuk, Julia A.; de Oliveira, Harley F.; Tone, Luiz G.; Brassesco, María S.
<x xml:space="preserve">Abstract</x> Polo-like kinase 1 (PLK1), a key regulator of mitosis, is often overexpressed in childhood cancers and is associated with poor prognosis. Previous reports have shown that inhibition of PLK1 might serve as a promising anticancer treatment for osteosarcoma. In this study, we tested the second-generation PLK1 inhibitors BI 6727 and GSK461364 in HOS and MG-63 cell lines, both as a single agent and in combination with methotrexate, cisplatin, vinblastine, doxorubicin, or ionizing radiation. Both PLK1 inhibitors worked equally in terms of cell growth arrest, apoptosis induction, and radiosensitization. Combining BI 6727 or GSK461364 with conventional treatments, however, showed trivial synergistic antitumor effects in vitro. Our results reinforce the potential use of PLK1 inhibitors for a pharmacologic intervention in osteosarcoma, although their applicability in polychemotherapeutic regimens deserves further investigation.